Adolescentes institucionalizados e sua relação com as drogas: uma abordagem de inspiração sociopoética - Moraes, Leila Memória Paiva (2003)
The society live a mass process of the use of psychoactive drugs that shows, in its origin, determínants ofsocio-economic and cultural order, peculiar ofthe contempo.ra.ry world. We call the attention to the abusive use of drugs among the youthful people. a group that have increased their consumption, We present as central problem: which voices resound in the inner of each of these institutionalized adolescents in the obscure drug world? We tríed to apprehend how the adolescent institutionalized perceives and experiences his contact with the drug. We purposed to apprehend the feelings of an adolescent group institutionalized. with respecto to their relation with drugs. For this, we seek; to exalt the feeling expression related to the use of drugs, through the Creative gadgets and identify the way how they experience the use of drugs in their quotidian. We developed this study with the Institutionalized youthfull people of a Public Asylum of Ceará Staste, that fòcuses its actions to the children and adolescents that are, according to its statutes, in situation ofsocial and personal risk, We considered to be indispensable the use of a methodology that drove us to an innovator study. We inspired ourselves on the sociopoetic through the method ofthe Reseacher-Group and through the subsidies of the Institutional Analysis, helping this way the expression of creativity and sensitivity, the freedom expression and also the revolutionary emerging of the group through the 1ífe workshops. We detached with the study that the adolescent group had already contact with the drugs, recognízing the relation between violence and pleasure. The seeking for pleasure and the escapement from their life conditíons are considered by them as inductors of the use, remaining to them marks that will never be eliminated. Thus, this relation between drugs, violence and pleasure is experienced in a conflictive way and surrounded by multíple feelings, such as: expectation, fury, hopelessness, affliction, resignation, and nonresignation. Factors such as the absence of the family, society prejudice, and the lack of perspective are aspects that sadden these youthful people. The relation that they show to have with the drug is of love and hate, The religious side also appears as a powerful artífice to escape from this intrinsic relation between drugs, violence and pleasure. All this collective construction has marks of our footprints and tints of a painted watercolour for several hands, where the colours stetch feelings, shared experiences as an unfinished work and in constant transformation. The outline producted here try to paint a little of the visited la.ndscapes an the appreciated melodies in this immense accomplished journey by the harmonious btrds songs (co-researchers) along all the process of production and analysis of the data. ín the end of this journey, we are sure that, even being just an aproximatíon of this reality, it was a rich and remarkable experience for all that were involved in this process.